Elucidation of ustilaginoidin biosynthesis reveals a previously unrecognised class of ene-reductases. Issue 44 (3rd November 2021) - Xu, Dan; Yin, Ruya; Zhou, Zhiyao; Gu, Gan; Zhao, Siji; Xu, Jin-Rong; Liu, Junfeng; Peng, You-Liang; Lai, Daowan; Zhou, Ligang
Abstract : The 2, 3-double bond reduction of the pyrenone ring in linear naphtho-γ-pyrenones was catalyzed by a phospholipid methyltransferase-like enzyme, namely UsgR, which is a previously unrecognised class of ene-reductases. Abstract : Ustilaginoidins are a type of mycotoxin featuring a dimeric naphtho-γ-pyrone skeleton, produced by the rice false smut pathogen Ustilaginoidea virens . Here we used gene disruption, heterologous expression in Aspergillus oryzae, feeding experiments, and in vitro experiments to fully elucidate the biosynthesis of ustilaginoidins. A new route to dimeric 2, 3-unsaturated naphtho-γ-pyrones via dimerization of YWA1 (and 3-methyl YWA1) followed by dehydration was discovered. Intriguingly, the reduction of the 2, 3-double bond of the pyrenone ring was catalyzed by a phospholipid methyltransferase-like enzyme (UsgR). The reductase was specific for reduction of monomeric, linear naphtho-γ-pyrenones, but not for the dimers. Atroposelective coupling of various monomers by the laccase (UsgL) led to diverse ustilaginoidins. Moreover, 3-epimerism of the 3-methyl-2, 3-dihydro-naphtho-γ-pyrones adds additional complexity to the biosynthesis.